Representing “Otherness”: Animals in Alice’s Adventures in Wonderland, The Hundred and One Dalmatians, and Beyond - Piu DasGupta (Leaf Journal)
In this article, I examine the portrayal of animals in Lewis Carroll’s Alice’s Adventures in Wonderland and Dodie Smith’s The One Hundred and One Dalmatians. Specifically, I consider the issue of the alterity (or “otherness”) of animals as a category, and the extent to which this is reflected (or not) in these two texts. I then proceed to consider this question in relation to more recent children’s books and my own practice as a writer. This article reflects on and develops, in the context of the specific texts cited above and my personal practice as a writer, the discussion by Mimi Thebo of animal representation in children’s literature in her article ‘Talking Tigers: Concepts of Representational Ethics Applied to Non-Human Characters in Writing Children’s Fiction’.